'It Depends': Technology Use by Parent and Family Educators in the United States - Susan K. Walker (MDPI AG, 2019)
Using data from a national sample of parent and family educators in the US (n = 697), this comparative study examines professionals' practices and technology-related attitudes, skill and workplace conditions. Overall, professionals report positive attitudes about the value of using technology in practice and view themselves as proficient. They most frequently use technologies like the email and document preparation software, and less frequently social media and even virtual reality. Workplace resources vary significantly, educators are not motivated by employer expectations and most report self-training as more valuable than formal sources. Mean comparisons by family educator type validate differences by context. Parenting educators, occasional family educators (e.g., teachers, counselors) and Family Life Educators vary from those in Higher Education/Administration. Those in Higher Education/Administration have more technology resources, report more positive attitudes, are more confident about their skills, and view formal technology training as useful. Conclusions suggest the need for the field of parent and family education to join other educational professions (e.g., licensed classroom teachers) to embrace technology use as a critical competency and advocate for the necessary resources in the preparation and ongoing service training of professionals.